Research and development technique for estimating airflow and diffusion parameters in connection with the Atmospheric Water Resources Program: interim report - Cermak, J. E. (Jack E.), author; Grant, Lewis O., author; Orgill, Montie M., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1969)
Preliminary experiments on transport and dispersion over a 1:9,600 scale model of the Eagle River Valley and topography surrounding Climax, Colorado were obtained in the Colorado State University meteorological wind tunnel. Geometric, dynamic and thermal similarity are considered, primarily, for neutral stability flows. Similarity for transport and dispersion is considered briefly. Pilot balloon flights, a super pressure balloon flight and ice nuclei concentrations taken during a field trip in the Climax area are presented.
CER68-69JEC-LOG-MMO27.
February 1969.
Period July 1, 1968 to December 31, 1968, atmospheric water resources research for the Bureau of Reclamation.
Keywords: Atmospheric diffusion; Air flow; Fluid dynamics